Assessment of the Frequency of Anterior Non Metric Traits A Cross sectional Study - Aiswarya G R 22B10101; Dr Sreeshyla H S (JSS AHER , Mysuru JSSDCH, Mysuru, 2024)
1. Introduction 2.Objectives 3.Literature Review 4. Materials & Methods 5. Results 6.Discussion & Limitations 7.Conclusion 8. Summary 9. References 10. Annexure